A model of ballistic helium transport during helium-induced fuzz growth in tungsten. (March 2023) - Patino, M.I.; Doerner, R.P.; Baldwin, M.J.; Tynan, G.R.
Abstract: Ballistic helium transport in tungsten during fuzz growth was investigated to provide insight into the helium-induced nanostructuring process which adversely affects the near-surface properties of tungsten plasma-facing components. An analytical model of helium ion transport in the vacuum region within the fuzz layer was developed, whereby He ions are assumed to move in straight-line trajectories with mean free paths determined from fuzz/nanotendril dimensions. Reflection of ions from tendril sides was considered, with He ions allowed to implant into the bulk at the base of the fuzz layer if they maintain ≥ 5 eV of energy necessary to overcome the He–W surface barrier potential, resulting in an increase in the effective He mean free path. Using the model results for helium implantation in the bulk, a helium fluence-fuzz thickness relation was achieved, which matches well with experimental data in the literature, and implies that the fuzz growth rate is consistent with ballistic implantation into the bulk through the growing porous fuzz layer. Highlights: A numerical model of ballistic helium transport in tungsten fuzz was developed. The helium mean free path in the fuzz layer was increased by considering the reflection of ions from tendril sides. The experimentally observed growth rate of fuzz was successfully reproduced when considering ballistic helium implantation into the bulk at the fuzz base.